GREEN BUILDING POLICY FORMULATION IN THE MUNICIPALITY OF BANDUNG INDONESIA - Engkus Engkus (Sosiohumaniora, 2019)
Land use that is not based on spatial planning based on green building concepts. This study aims to find out how the formulation of Bandung Mayor Regulation Number 1023 of 2016 concerning Green Buildings tested the system model(David, 1981). This study uses a qualitative approach with actual problems that occur in life (Engkus E, 2017). Policy formulation uses 5 (five) dimensions, namely input, process, output, environment, feedback. The results show that there are problems: a more complex green building policy, imposed on all buildings including housing; lack of community knowledge and understanding of the concept of green buildings, so that the community participates less; limited green building policy dissemination.